Kepastian Hukum dan Prinsip Ekonomi Syariah dalam Bisnis Digital Nelayan Kecil pada Aplikasi Nelpin di Juwana Pati - Mungawanah, Novia (Sharia Faculty Islamic Economic Law Study Department, 2025)
In the digital era, information and communication technology (ICT) is viewed as a solution to strengthen the bargaining position of small-scale fishers, enhance operational efficiency, and improve their overall welfare. The digital innovation Nelayan Pintar (Nelpin), designed by the Ministry of Marine Affairs and Fisheries (KKP), represents a significant breakthrough in Indonesia’s national fisheries system. The Nelpin application assists fishers in identifying potential fishing zones, providing information on weather conditions, water fertility, wave and wind heights, ports, fish prices, fuel consumption estimates, and various marine-related assistance programs. This study aims to describe how the Nelpin application functions in practice and to assess the extent to which regulations provide legal certainty for digital transactions, data protection, and the rights of small-scale fishers. The research employs a normative juridical method, which focuses on positive legal norms, principles, and applicable legal doctrines as the primary basis for analyzing the identified legal issues. Legal materials were collected using a purposive sampling technique, selecting documents and regulations relevant to the research focus. In the context of Islamic economics, the implementation of the Nelpin application should also align with fundamental principles such as justice (al-‘adl), public benefit (maslahah), cooperation (ta‘awun), and the prohibition of exploitation (gharar and riba). These principles emphasize the importance of transparency, honesty, and fair distribution of benefits between service providers and small-scale fishers. Therefore, the digitalization of the marine and fisheries sector through Nelpin is expected not only to provide legal certainty but also to reflect the values of social justice and collective welfare as envisioned in the Islamic economic system.